The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1038/s41531-021-00228-0
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive subtyping of Parkinson’s disease patients with similarity fusion: a case study with BioFIND data

Abstract: Parkinson’s disease (PD) is a complex neurodegenerative disorder with diverse clinical manifestations. To better understand this disease, research has been done to categorize, or subtype, patients, using an array of criteria derived from clinical assessments and biospecimen analyses. In this study, using data from the BioFIND cohort, we aimed at identifying subtypes of moderate-to-advanced PD via comprehensively considering motor and non-motor manifestations. A total of 103 patients were included for analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Specifically, we first split the entire cohort into 5 folds, then each time, we successively dropped 1 fold (20% children) and used the remaining 4 folds (80% children) to construct a subset. 48 We then re-identified SDoH patterns in each subset. In both sensitivity analyses, patterns of SDoH were re-identified using the hierarchical clustering algorithm, following the same criteria as in the primary analysis for determining the optimal number of clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we first split the entire cohort into 5 folds, then each time, we successively dropped 1 fold (20% children) and used the remaining 4 folds (80% children) to construct a subset. 48 We then re-identified SDoH patterns in each subset. In both sensitivity analyses, patterns of SDoH were re-identified using the hierarchical clustering algorithm, following the same criteria as in the primary analysis for determining the optimal number of clusters.…”
Section: Discussionmentioning
confidence: 99%
“…However, combining both motor and NMS could be of great interest and usefulness [ 6 , 7 ]. Very recently, Brendel et al [ 51 ], using data from the BioFIND cohort with clustering analysis, identified three unique subtypes: subtype I, characterized by mild symptoms, both motor and non-motor; subtype II, characterized by an intermediate severity, with a high tremor score and mild non-motor symptoms; and, subtype III, with more severe motor and non-motor symptoms. Although different biological markers may be useful in the future when classifying PD for its management (i.e., genetic, neuroimaging, biochemical, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Another aim of precision medicine is to provide tailored treatment to individual patients, which can be achieved by classifying patients into finely grained disease subtypes that respond better to certain treatments. Unsupervised ML ( Box 1 ) methods like clustering ( Box 1 ) approaches and latent class ( Box 1 ) can reveal such subtypes ( Brendel et al, 2021 ). Precision medicine also aims to identify treatment tailored to a specific stage of a disorder.…”
Section: Precision Medicine Requires Deep Genomic and Phenotypic Datamentioning
confidence: 99%